(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Originating in Wuhan, China, the epidemic of coronavirus disease 2019 (COVID-19) has become a major public health challenge for not only China but also countries around the world. The outbreaks of the novel coronavirus have constituted a public health emergency of international concern as announced by the World Health Organization (WHO). For dental care provision to active or suspected COVID-19 cases, no universal protocol or guideline is available till date. Major challenges to worldwide health systems will have farreaching consequences on the global economy if the spread of the virus is not effectively controlled as a consequence of the COVID-19 outbreak. So, in a nutshell, there is no point in being cynical about the future of the dental profession.